Religious studies, faith, and the presumption of naturalism - Dawes, Gregory W. (The journal of religion & society, 2003)
In a recent defence of what he calls "study by religion," Robert Ensign suggests that alleged divine revelations represent public forms of knowledge, which should not be excluded from the academy. But at least according to two major Christian thinkers, namely Thomas Aquinas and John Calvin, revelation is received by an act of faith, which rests on evidence that is person-relative and therefore not open to public scrutiny. If religious studies is to remain a public discipline, whose arguments may be evaluated by believers and non-believers alike, it should maintain its defeasible but not yet defeated presumption of naturalism.